Color Gamut Behavior in Epsilon Near‐Zero Nanocavities during Propagation of Gap Surface Plasmons. Issue 17 (10th June 2020) - Lio, Giuseppe Emanuele; Ferraro, Antonio; Giocondo, Michele; Caputo, Roberto; De Luca, Antonio
Abstract: This work reports on numerical and experimental results obtained in plasmonic metal–insulator nanocavities. The systems are composed of silver as metal, and different materials as insulator, namely polyvinylpyrrolidone (PVP), indium tin oxide (ITO), and zinc oxide (ZnO). The proposed nanocavities exhibit extraordinary optical effects as tunable color hue, highlighted in gamut maps, depending on incident/viewing angles, extraordinary transmission and zero reflection at resonant wavelengths, for different incident polarizations. These phenomena are related to the formation of surface plasmon polaritons (SPPs) and gap surface plasmons (GSPs) whose presence is evidenced by a remarkable sigmoidal behavior of the pseudo dielectric function, with epsilon‐near‐zero singularities in its real and imaginary parts. This function is directly calculated from the measured ellipsometric parameters Ψ and Δ and allows probing, in a fast and effective way, the existence of the plasmonic modes. Moreover, in presence of these singularities, the ellispometric analysis of the systems also shows a pronounced dephasing between p‐ and s‐reflected beams that can lead to a Goos–Hänchen shift effect to be exploited for sensing applications. Thanks to their unusual optical properties, the proposed nanocavities open a wide scenario of applications in fields like tunable color filters, optics, photonics, physical security, and sensing. Abstract : The proposed multilayered structures enable the propagation of gap surface plasmons (GSPs) and surface plasmon polaritons (SPPs) that are reflected in a color hue. Due to their presence, the optical and ellipsometer features show enormous jumps in terms of dephasing. The incredible chromaticity of the systems are shown in the gamut map, where the color variation depends on reflectance/transmittance angles or in other words incidence/view angles.